Sexual Content in Young Adult Literature: Reading between the Sheets - Gillis, Bryan; Simpson, Joanna (Rowman & Littlefield Publishers, 2015)
Though discussing sexual material in novels aimed at the young adult market may make some individuals blush, the authors of such fiction often seek to represent a very real component in the lives of many teens. Unfortunately, authentic and teen-relatable information on healthy adolescent sexuality is not readily available, and sex education classes have had a minimal effect on positive sexual identity development. Consequently, young adult literature that contains sexual elements can play a critical role in addressing the questions and concerns of teens. In Sexual Content in Young Adult Fiction: Reading between the Sheets, Bryan Gillis and Joanna Simpson examine sexual material in canonical, historical, dystopian, romantic, and realistic contemporary fiction for teens. The authors begin with an exploration of sexual identity development and discuss the constructive influence that realistic representations of teen sexual behavior can have on that development. The authors provide a myriad of texts and examples that will help parents, teachers, and librarians better understand the positive role that sexual content in YA fiction can play in the socio-emotional and academic development of adolescents. The book concludes with an overview and analysis of censorship in the world of young adult fiction. In addition to providing a survey of sexual content in young adult literature, this book can help inspire adults to facilitate effective and responsible discussions about young adult fiction that contains sexual material. Featuring a "novels cited" and "works cited" bibliography, Sexual Content in Young Adult Fiction is an important resource that parents and educators will find particularly valuable.